PENGABDIAN MASYARAKAT DAN PENINGKATAN KINERJA BISNIS DARI USAHA MIKRO EGK - Astuti, Miguna; Rizkita Amanda, Agni; Marlina; Gunaedi Argo, Jenji; Surya Kusuma, Airlangga (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
The ‘Edukasi Gemilang Kencana’ (EGK) business is located in the Depok area, West Java. Even though it has been around for quite some time, due to the Covid-19 pandemic, the Micro enterprosise EGK has been inactive. Some of the problems identified in EGK businesses include: (1) Low understanding of the staff regarding the importance of social media accounts for business marketing activities; (2) Staff’s in is still low in carrying out marketing activities using social media accounts; (3) Staff's understanding is still low regarding the importance of websites for business marketing activities; (4) Staff's understanding and skills are still low in managing social media and websites. Previously, EGK Partners only carried out conventional marketing activities, and had not implemented any digital marketing such as the electronic customer relationship management (E-CRM) activities such as social media and websites. Even when all points toward increase on market share, turnover and even business profits if business would be willing to implement E-CRM. So, the team then offered several solutions, including: (1) Training related to the importance of social media accounts for business performance; (2) Assistance in creating an official EGK Instagram social media account; (3) Training related to the importance of websites for business performance; (4) Assistance in creating the official EGK website. The results of the activities show that an increase in partners' knowledge and skills regarding E-CRM has been achieved. These increases include: (1) Knowledge regarding the importance of Social Media Accounts increased by 72.73%; (2) Skills in using social media accounts for business marketing activities increased by 71.13%; (3) Understanding and skills related to websites for business marketing activities increased by 100%; (4) Launching of the official EGK business Instagram account; (5) Launching of the official EGK website; (6) Increase in market share by 85%; (7) increase in turnover by 85%. The activity is also expected to contribute to the achievement of Sustainable Development Goals (SDGs) 1, 8 and 10 as well as contribute to the field of management science, especially digital marketing management ABSTRAK Mitra EGK merupakan sebagai salah satu usaha yang berdomisili di wilayah Depok Jawa Barat. Meski telah berdiri cukup lama, namun dikarenakan Pandemi Covid-19, usaha mikro Edukasi Gemilang Kencana (EGK) sempat mengalami kevakuman. Beberapa permasalahan yang teridentifikasi pada usaha mitra EGK antara lain yaitu: (1) Pemahaman SDM masih rendah terkait pentingnya akun media sosial bagi kegiatan pemasaran usaha; (2) Keterampilan SDM yang masih rendah dalam menjalankan kegiatan pemasaran dengan menggunakan akun media social; (3) Pemahaman SDM yang masih rendah terkait pentingnya website bagi kegiatan pemasaran usaha; (4) Pemahaman dan keterampilan SDM yang masih rendah dalam mengelola media sosial dan website. Mitra EGK sebelumnya hanya melakukan kegiatan pemasaran yang bersifat konvensional, dan belum melaksanakan kegiatan E-CRM seperti social media dan website, padahal hal tersebut mampu meningkatkan pangsa pasar, omset dan bahkan profit usaha. Sehingga tim pengabdian menawarkan beberapa solusi, antara lain: (1) Pelatihan terkait pentingnya akun media sosial bagi kinerja bisnis; (2) Pendampingan pembuatan akun media sosial Instagram resmi EGK; (3) Pelatihan terkait pentingnya website bagi kinerja bisnis; (4) Pendampingan pembuatan website resmi EGK. Hasil kegiatan memperlihatkan peningkatan pengetahuan dan keterampilan mitra terkait CRM & E-CRM telah tercapai. Adapun peningkatan tersebut termasuk pada: (1) Pengetahuan terkait pentingnya Akun Media Sosial meningkat sebesar 72,73% ; (2) Keterampilan dalam menggunakan akun media social untuk kegiatan pemasaran usaha meningkat sebesar 71,13%; (3) Pemahaman dan keterampilan terkait website bagi kegiatan pemasaran usaha meningkat sebesar 100%; (4) Terpublishnya akun Instagram bisnis resmi EGK; (5) Terpublishnya website resmi EGK; Peningkatan pangsa pasar sebesar 85%; peningkatan omset sebesar 85%. Kegiatan tersebut juga diharapkan dapat memberikan kontribusi terhadap pencapaian Sustainable Development Goals (SDGs) 1,8 dan 10 serta memberikan kontribusi pada bidang ilmu manajemen khususnya manajemen pemasaran digital